008 Spontaneous cardiac hypertrophy and identification of novel hypertrophic pathways in a genetic mouse model that emulates human diabetes. (22nd September 2015) - Gibbons, S M; Hegab, Z; Zi, M; Prehar, S; Mohammed, T; Oceandy, D; Goldsworthy, M; Cox, R D; Cartwright, E; Neyses, L; Mamas, M A
Abstract : Animal models are key in the exploration of the pathophysiological mechanisms and complications of diabetes mellitus (DM). Most current models have considerable limitations in that they do not faithfully replicate human forms of DM. Recently, a novel human relevant mouse model of diabetes (GENA 348) was identified through the Medical Research Council, Harwell, UK mouse mutagenesis programme in which a point mutation in the glucokinase gene results in severely impaired glucokinase function and significant hyperglycaemia. Similar mutations in the glucokinase gene are known to underlie Maturity Onset Diabetes of the Young Type 2 (MODY 2) in humans. We studied the GENA 348 mouse to determine whether it expresses a cardiac phenotype to provide insight into the pathophysiological mechanisms underlying the development of diabetic cardiomyopathy. Fifteen wild type (WT) controls and eight homozygote mutant (HO) mice had serial echocardiography performed at 3 and 6 months. At 3 months no evidence of cardiac hypertrophy or contractile dysfunction was demonstrated in HO compared to WT mice. By 6 months of age, echo demonstrated development of cardiac hypertrophy in GENA 348 HO mice characterised by a 16% increase in left ventricular mass/body weight (wt 4.28±0.15 vs HO 4.95±0.26, p<0.05), a 25% increase in dPW/dD (WT 23.3±1.0 vs HO 29.1±1.1, p<0.01) and an 18% increase in left ventricular relative wall thickness (WT 0.45±0.01 vs HO 0.53±0.02, p<0.05). No differences in systolic function were observed although significant diastolic dysfunction was also evident with a 31% reduction in the E:A ratio (WT 2.65±0.2 vs HO 1.84±0.19, p<0.05) and a 34% increase in the IVRT (WT 15.2±1.1 ms vs HO 20.5±0.37 ms, p<0.01). Histological staining illustrated cellular hypertrophy with a 60% increase in cardiomyocyte size (WT 238±14 μm 2 vs HO 383±26 μm 2, p<0.001). Hypertrophic pathways were examined through western blot analysis, a 140% increase in Akt phosphorylation, a key mediator of cardiac hypertrophy and a 65% increase in GSK3β phosphorylation one of its key regulators was observed. We also demonstrate that advanced glycation end products (AGE) were elevated by 86% in the serum of mutant GENA 348 mice. Collectively, these data indicate GENA 348 mutant mice develop a cardiac phenotype including hypertrophy and diastolic dysfunction similar to the clinical manifestations of diabetic cardiomyopathy. Furthermore, a novel hypertrophic pathway has been identified in which AGE stimulation through GSK3β leads to activation of the intracellular Akt pathway. GENA 348 may thus provide a valuable, human-relevant tool for studying the molecular determinants of DM related cardiovascular complications.